Utility-based scheduling algorithms to enhance user satisfaction in OFDMA systems - Costa Neto, Francisco Hugo (2016)
The increasing market demand for wireless services and the scarcity of radio resources calls more than ever for the enhancement of the performance of wireless communication systems. Nowadays, it is mandatory to ensure the provision of better radio services and to improve coverage and capacity, thereby increasing the number of satisfied subscribers. This thesis deals with scheduling algorithms aiming at the maximization and adaptive control of the satisfaction index in the downlink of an Orthogonal Frequency Division Multiple Access (OFDMA) network, considering different types of traffic models of Non-Real Time (NRT) and Real Time (RT) services; and more realistic channel conditions, e.g., imperfect Channel State Information (CSI). In order to solve the problem of maximizing the satisfaction with affordable complexity, a cross layer optimization approach uses the utility theory to formulate the problem as a weighted sum rate maximization. This study is focused on the development of an utility-based framework employing the shifted log-logistic function, which due to its characteristics allows novel scheduling strategies of Quality of Service (QoS)-based prioritization and channel opportunism, for an equal power allocationn among frequency resources. Aiming at the maximization of the satisfaction of users of NRT and RT services, two scheduling algorithms are proposed: Modified Throughput-based Satisfaction Maximization (MTSM) and Modified Delay-based Satisfaction Maximization (MDSM), respectively. The modification of parameters of the shifted log-logistic utility function enables different strategies of distribution of resources. Seeking to track satisfaction levels of users of NRT services, two adaptive scheduling algorithms are proposed: Adaptive Throughput-based Efficiency-Satisfaction Trade-Off (ATES) and Adaptive Satisfaction Control (ASC). The ATES algorithm performs an average satisfaction control by adaptively changing the scale parameter, using a feedback control loop that tracks the overall satisfaction of the users and keep it around the desired target value, enabling a stable strategy to deal with the trade-off between satisfaction and capacity. The ASC algorithm is able to ensure a dynamic variation of the shape parameter, guaranteeing a strict control of the user satisfaction levels. System level simulations indicate the accomplishment of the objective of development of efficient and low complexity scheduling algorithms able to maximize and control the satisfaction indexes. These strategies can be useful to the network operator who is able to design and operate the network according to a planned user satisfaction profile.